Squatina caillieti sp. nov., a new species of angel shark (Chondrichthyes: Squatiniformes: Squatinidae) from the Philippine Islands - Walsh, Jonathan H.; Ebert, David A.; Compagno, Leonard J. V. (Zootaxa, 2011)
A new species of angel shark, Squatina caillieti sp. nov., is described from a single specimen collected in deepwater off Luzon in the Philippines. The new species is closest to S. formosa and S. nebulosa, but differs from its congeners based on the following characters: unfringed barbels with rod-like tips, upper lip arch semi-oval in shape, large papillae present on the inside posterior margin of the spiracles, a greater interspiracle space than interorbital space, pelvic fin-tips which reach the first dorsal origin, a short pelvic fin base, short pelvic inner margin very short, and a short pelvic posterior margin; pelvic girdle span more than 1.4 times greater than head length; dorsal fins angular, greater interdorsal space than dorsal caudal space; caudal fin lobed, very short upper postventral caudal margin. The new species is the only Squatina confirmed as occurring in the Philippines. We also comment on the biogeography of western North Pacific Squatina and provide a revised regional key to this group.